Analisis Peran Guru Dalam Meningkatkan Motivasi Belajar Siswa Kelas V SD Negeri 060938 Medan Johor Tahun Pembelajaran 2022/2023 - Rika Monika Manurung; Antonius Remigius Abi; Reflina Sinaga; Juliana Juliana; Nova Florentina (Departement of Mathematics Education, 2023)
The purpose of this study was to determine the role of teachers in increasing the motivation of fifth grade students of SD Negeri 060938 Medan Johor. The benefit of this research is to add insight related to the role of teachers in increasing student motivation. Based on research conducted at SD Negeri 060938 Medan Johor, it can be seen that the role of teachers in increasing student learning motivation based on aspects of arousing student interest, creating a pleasant atmosphere in learning, commenting on student work, creating competition and cooperation, and giving punishment is quite good, because teachers have been able to design lessons that can develop learning motivation and make them feel happy and comfortable, homeroom teacher V is also able to give thorough comments to each student's success and is able to create competition and cooperation so as to build cooperation between students in the classroom and give punishment to students in order to motivate students. The role of homeroom teacher V in developing student learning motivation based on aspects of clarifying the goals achieved, providing assessment and giving reasonable praise for each student's success has indeed been carried out but in its implementation, it has not been maximized. Teachers in giving praise have not been thorough, but only given to students who are active during the learning process and teachers also in giving assessments have not been thorough, teachers are more dominant in assessing knowledge to students. This shows that the teacher's role in increasing learning motivation has been carried out but has not been maximized.